Overexpression of Tbx20 in Adult Cardiomyocytes Promotes Proliferation and Improves Cardiac Function After Myocardial Infarction. Issue 11 (15th March 2016) - Xiang, Fu-li; Guo, Minzhe; Yutzey, Katherine E.
Abstract : Background—: Adult mammalian cardiomyocytes (CMs) have the potential to proliferate, but this is not sufficient to generate adequate CMs after myocardial infarction (MI). The transcription factor Tbx20 is required for CM proliferation during development and adult CM homeostasis. The ability of Tbx20 overexpression (Tbx20 OE ) to promote adult CM proliferation and to improve cardiac function after MI was examined. Methods and Results—: Tbx20 OE was induced specifically in adult mouse differentiated CMs. Increased CM proliferation and fetal-like characteristics were found in Tbx20 OE hearts compared with controls without causing pathology 4 weeks after Tbx20 OE at baseline. Moreover, Tbx20 OE in adult CM after MI significantly improved survival, cardiac function, and infarct size 4 weeks after MI. Improved cardiac repair, as indicated by increased CM proliferation and capillary density, was observed in the MI border zone of Tbx20 OE hearts compared with controls. Expression of proliferation activator ( cyclin D1, E1, and IGF1 ) and fetal contractile protein ( ssTNI, βMHC ) mRNA was increased whereas negative cell-cycle regulators ( p21, Meis1 ) were decreased in Tbx20 OE hearts compared with controls under both baseline and MI conditions. Tbx20 OE in adult hearts activates multiple proproliferation pathways, including Akt, YAP and BMP. Interestingly, p21, Meis1, and a novel cell-cycle inhibitory gene, Btg2, are directly bound and repressed by Tbx20 with induction of proliferation in neonatal CM. Conclusions—: Tbx20 OE, specifically in adult CM, activates multiple cardiac proliferative pathways, directly represses cell-cycle inhibitory genes p21, Meis1, and Btg2, promotes adult CM proliferation; and preserves cardiac performance after MI. Abstract : Supplemental Digital Content is available in the text.